The Impact of Virtual Reality as a Rehabilitation Method Using TRAVEE System on Functional Outcomes and Disability in Stroke Patients: A Pilot Study - Claudia-Gabriela Potcovaru; Delia Cinteză; Miruna Ioana Săndulescu; Daniela Poenaru; Ovidiu Chiriac; Cristian Lambru; Alin Moldoveanu; Ana Magdalena Anghel; Mihai Berteanu (Biomedicines)
Background: Stroke is the third leading cause of disability. Virtual reality (VR) has shown promising results in post-stroke rehabilitation. The VR TRAVEE system was designed for the neuromotor rehabilitation of the upper limb after a stroke and offers the ability to track limb movements by providing auditory feedback and visual augmentation. The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), aligned with the International Classification of Functioning, Disability, and Health (ICF) principles, is a valid tool for measuring disability regardless of its cause. This study aimed to investigate the feasibility of the VR TRAVEE system in upper limb rehabilitation for stroke patients. Methods: A total of 14 stroke patients with residual hemiparesis were enrolled in the study. They underwent a 10-day program combining conventional therapy (CnvT) with VR rehabilitation. At baseline (T0), the upper limb was assessed using the Modified Ashworth Scale (MAS), active range of motion (AROM), and the Numeric Rating Scale (NRS) for pain. These assessments were repeated after the 10-day rehabilitation program (T1). Additionally, disability was measured using WHODAS 2.0 at T0 and again 30 days after completing the program. Results: Significant improvements were observed in AROM and MAS scores for the shoulder, elbow, wrist, and metacarpophalangeal joints, as well as in the reduction in shoulder pain (p ˂ 0.001). WHODAS scores decreased across all six domains, with a statistically significant improvement in the Cognition domain (p = 0.011). Conclusions: Combining CnvT with VR as a rehabilitation approach enhances motor function in the upper limb. This method has the potential to reduce disability scores and promote neuroplasticity.